Managing risk in extreme environments front-line business lessons for corporates and financial institutions - Martin, Duncan; Gale Group (London, England Kogan Page, 2008)
Presents real-life examples of extreme situations - from epidemics to earthquakes - to showcase risk management strategies which have been tested and shown to succeed.
Epidemic -- Wildfire -- Terrorism -- Extreme humanitarian aid -- Mountain -- Meltdown -- Extraction -- Flood -- Earthquake -- Managing risk in extreme environments -- So what? -- The seven laws of extreme risk management.
Electronic reproduction.
Mode of access: Internet.
Keywords: Risk management; Emergency management; Electronic books